Transportation resilience to climate change and extreme weather events – Beyond risk and robustness. (February 2019) - Markolf, Samuel A.; Hoehne, Christopher; Fraser, Andrew; Chester, Mikhail V.; Underwood, B. Shane
Abstract: The long-term reliability and functioning of transportation systems will increasingly need to consider and plan for climate change and extreme weather events. Transportation systems have largely been designed and operated for historical climate conditions that are now often exceeded. Emerging knowledge of how to plan for climate change largely embraces risk-based thinking favoring more robust infrastructure designs. However, there remain questions about whether this approach is sufficient given the uncertainty and non-stationarity of the climate, and many other driving factors affecting transportation systems (e.g., funding, rapid technological change, population and utilization shifts, etc.). This paper examines existing research and knowledge related to the vulnerability of the transportation system to climate change and extreme weather events and finds that there are both direct and indirect "pathways of disruption." Direct pathways of disruption consist of both abrupt impacts to physical infrastructure and impacts via non-physical factors such as human health, behavior, and decision making. Similarly, indirect pathways of disruption result from interconnections with other critical infrastructure and social systems. Currently, the direct pathways appear to receive much of the focus in vulnerability and risk assessments, and the predominant approach for addressing these pathways of disruption emphasizes strengthening and armoring infrastructure (robustness) guided by risk analysis. However, our analysis reveals that indirect pathways of disruption can have meaningful impacts, while also being less amenable to robustness-based approaches. As a result, we posit that concepts like flexibility and agility appear to be well suited to complement the status quo of robustness by addressing the indirect and non-physical pathways of disruption that often prove challenging - thereby improving the resilience of transportation systems. Highlights: Climate change impacts on infrastructure can be exacerbated by issues like complexity and interconnected systems. Current focus of climate adaptation in transportation infrastructure may overlook behavioral and interconnected effects. Successful adaptation may require more than robustness (i.e., calculation of risk and subsequent hardening of infrastructure). Indirect vulnerabilities via interconnected infrastructure and non-physical vulnerabilities are less conducive to robustness.